Achieving Hybrid Cloud Cyber Resiliency with IBM Spectrum Virtualize for Public Cloud - IBM (IBM Redbooks, 2020)
This document is intended to facilitate the approach of achieving the Cyber Resiliency solution for IBM® Spectrum Virtualize for Public Cloud. This solution is designed to protect the data on IBM Spectrum"!Virtualize storage in a hybrid multicloud environment by deploying cloud backup to Amazon S3 using the function Transparent Cloud Tiering.